Growth and Yield of Inpari 29 Rice Varieties on Raised-bed and Different Depths of Sunken-bed in Saline Field - Nasrudin Nasrudin; Budiastuti Kurniasih (Jurnal Ilmu Pertanian, 2018)
Increased productivity of rice is required to meet the increasing food demand. Utilization of marginal lands, such as saline land is one of the solutions applicable to increase rice production. The objective of this study was to determine the growth and yield of Inpari 29 rice variety planted on raised-bed and different depths of sunken-bed in saline field. This study used the Split Plot Design with two treatments. The depth as the main plot consisted of two depth levels: a depth of 50 cm and a depth of 25; and the planting area field as the subplot that consisted of two levels: raised-bed and sunken-bed. The treatment was repeated three times. The rice planted in sunken-bed showed higher growth than in raised-bed as indicated by the high content of chlorophyll a, chlorophyll b, total chlorophyll, nitrate reductase activity and plant height. The rice planted in the sunken-bed yielded higher than in raised-bed as indicated by higher harvest index and the weight of grain per clump. Rice planted in 25 cm depth showed higher nitrate reductase activity and grain weight per clump than in 50 cm depth.